Assessing the Effectiveness of Dorsal Flap in Surgical Repair of Hypospadias by Tubularized Incised Plate Urethroplasty - Muhammad Ali Adnan, Masroor Ahmad Baloch, Jameeat Mal, Majid Hussain, Asadullah Awan, Muhammad Farhan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypospadias is a congenital abnormality of the urethral meatus opening which is located anywhere along the length of the penis except the tip of the glans. The management of this congenital disease is surgical and comprises orthoplasty, urethroplasty, glanuloplasty and cosmetic correction. Urethroplasty is the key step of surgical correction of hypospadias. . Tubularized incision plate (TIP) urethroplasty by dorsal flap is frequently used for distal hypospadias. The reason for the preference is usually wide acceptability of low post-surgical complications and optimum cosmetic results. Other techniques include urethral plate augmentation and urethral plate replacement. Aims: The aim of this study is to assess the effectiveness of dorsal flap assisted TIP urethroplasty in patients with hypospadias of recruited population. The effectiveness will be measured against postoperative outcomes such as wound rupture, wound necrosis, meatal stenosis, and urethrocutaneous fistula formation. Methodology: This prospective study was conducted on 11 primary hypospadias cases undergoing TIPU in Dr Ziauddin Hospital, Karachi for the period of one year from November 2020 to October 2021. The inclusion criteria included infants with distal and midshaft hypospadias with sufficient width of the urethral plate. Whereas individuals with proximal hypospadias or other factors complicating the surgical procedure were excluded from the study population. Result: The total number of participants included was 11 children. The age of participants varied between 18 – and 28 months with a mean age of 24.2 ± 3.1 months. The meatus opening was seen at the distal end near the coronal sulcus in 8 participants whereas 3 participants showed preoperative meatus opening in the distal third of the shaft. An immediate follow up was done at 2 weeks intervals to assess wound health and situation. 1 out of 11 infants showed wound dehiscence which was immediately corrected. A late follow up was carried out after 2-3 years, no case presented with significant complications such as urethrocutaneous fistula or stenosis of the meatus. Conclusion: the study shows measured the post-operative complications followed by TIP urethroplasty using a dorsal flap. Immediate complications showed a single case of wound dehiscence. Whereas all long term follows up after 2-3 years showed no significant complications. After predisposing the clinical outcomes of this research against and in favour of pre-existing literature, it is concluded that dorsal flaps assisted TIP urethroplasty is a safe surgical procedure and is effective in terms of avoiding postoperative complications in individuals with hypospadias.